2018
DOI: 10.1590/1414-431x20187138
|View full text |Cite
|
Sign up to set email alerts
|

Detection of sputum cofilin-1 as indicator of malignancy

Abstract: Cofilin-1 (CFL1), a small protein of 18 kDa, has been studied as a biomarker due to its involvement in tumor cell migration and invasion. Our aim was to evaluate CFL1 as an indicator of malignancy and aggressiveness in sputum samples. CFL1 was analyzed by ELISA immunoassay in the sputum of 73 lung cancer patients, 13 cancer-free patients, and 6 healthy volunteers. Statistical analyses included ANOVA, ROC curves, Spearman correlation, and logistic regression. Sputum CFL1 levels were increased in cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Further analysis is needed to assess their role in lymph node metastasis risk. However, CFL-1 levels association with dedifferentiation, infiltration depth, pathological staging, and presence of lymph node metastasis have also been found in other cancer types [ 11 13 , 37 , 38 ]. It is possible to speculate that the invasive margin may be region within the tumor that exhibits the highest levels of CFL-1, which increases aggressiveness and leads to local dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis is needed to assess their role in lymph node metastasis risk. However, CFL-1 levels association with dedifferentiation, infiltration depth, pathological staging, and presence of lymph node metastasis have also been found in other cancer types [ 11 13 , 37 , 38 ]. It is possible to speculate that the invasive margin may be region within the tumor that exhibits the highest levels of CFL-1, which increases aggressiveness and leads to local dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Other bodily fluids: The analysis of stool-derived DNA has been recently validated as a powerful diagnostic tool for colorectal cancer [107], while sputum DNA and protein content has promising potential in the context of lung cancer [108]. Pleural effusions, finally, are source of DNA biomarkers for lung cancer [109] and malignant pleural mesothelioma [110], and the presence of Epithelial Cell Adhesion Molecule (EpCAM) + microparticles allows distinction between malignant and non-malignant pleural effusions [111].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…In the present tissue spot, the stage IV samples expressed low cofilin-1 and high Twist-1 levels (data not shown). In contrast to these findings, a recent report indicated that sputum cofilin-1 levels were higher in T4 and N stage of lung cancer patients (27). Serum cofilin-1 levels were further reported to be increased in the advanced stage of patients with lung cancer (28).…”
Section: Discussionmentioning
confidence: 91%